Poor compliance with the antibiotic policy in the intensive care unit (ICU) of a tertiary care hospital in India - Tuhina Banerjee; Shampa Anupurba; Dinesh K Singh (Journal of Infection in Developing Countries)
Introduction: Most developing countries are adopting antibiotic policies to contain the acute problem of drug resistance; however, several obstacles prevent their fulfillment. This study was undertaken to prospectively determine the compliance with the antibiotic policy in the intensive care unit (ICU) of a tertiary care hospital and possible reasons for non-compliance. Methodology: Compliance with the newly introduced antibiotic policy was studied for a period of six months. A total of 170 cases from the ICU were included. Relevant information regarding patient characteristics, treatment details, infection control, and antibiotic prescribing practices in the ICU with reference to the antibiotic policy was collected. Reasons for non-compliance were studied. Results: The rate of compliance with the antibiotic policy was 21.18%. Heavy use of antibiotics prior to the time of admission in the ICU was the major cause of non-compliance. Microbiological investigation had been sent in only 51.17% of the cases and change in treatment protocol based on culture report was done in 53.3%. The rate of use of third-generation cephalosporins was 76.78%. Conclusions: We found non-compliance with the antibiotic policy in the ICU mainly due to improper and inappropriate antibiotic usage in other indoor units of the hospital. In our case, a policy covering the entire hospital is required to meet the goals of antibiotic usage restriction. An effective surveillance, review, and evaluation process should be an integral part of the policy, even in developing countries, to measure the effects of such policies.